HIV testing in colposcopy and termination of pregnancy services: a missed opportunity?. Issue 4 (11th August 2011) - Briggs, Aparna; Partridge, David G; Bates, Sylvia
Abstract : Introduction: The 2008 National HIV testing guidelines produced jointly by the British Association of Sexual Health and HIV, British HIV Association and British Infection Society recommend HIV testing for patients attending termination of pregnancy (TOP) services and patients diagnosed with cervical intraepithelial neoplasia (CIN) Grade 2 or above. The aim is to reduce the time between acquisition and diagnosis of HIV by encouraging testing in settings where patients present with indicator diseases. Benefits of earlier HIV diagnosis include improved survival, prevention of onward transmission, and optimisation of maternal health when planning pregnancy. There is evidence that HIV reduces the effectiveness of standard treatment for CIN 2/3 and cervical cancer. The experience of antenatal screening indicates that the majority of women accept HIV screening if it is offered as part of a package of care. Methods: This retrospective case notes review of 60 HIV-positive women, diagnosed between 1 January 2006 and 31 July 2009, collected data on age, ethnicity, length of time in the UK, timing of HIV diagnosis and possible timing of acquisition relative to attendance at colposcopy or TOP services, CD4 count and symptoms at diagnosis and cervical cytology history. Results: The authors found that three (5%) women were diagnosed with CIN Grade 2 or above prior to HIV diagnosis; HIV testing at the time of TOP may have resulted in earlier diagnosis for three (5%) women. There was at least one missed opportunity for earlier diagnosis in five (8%) cases. Conclusions: The authors suggest further work should be undertaken to establish HIV prevalence in TOP and colposcopy services and that HIV testing should become standard practice in the management of CIN 2/3 and cervical cancer.